Predatory midges of the genus Schizohelea Kieffer, 1917 in Europe and North Africa (Diptera: Ceratopogonidae) - Szadziewski, Ryszard; Dominiak, Patrycja; Rumišek, Mario; Neinhuis, Christoph; Wanke, Stefan; Rupp, Thomas (Zootaxa, 2024)
Five species of the Holarctic genus Schizohelea occurring in Europe and North Africa are reviewed, diagnosed and illustrated. These are S. leucopeza (Meigen, 1804), S. incerta (Clastrier, 1963), S. algeriana Szadziewski, Dominiak, Rumišek et Rupp, sp. nov., S. clastrieri Szadziewski, Dominiak, Rumišek et Rupp, sp. nov. and S. withersi Szadziewski, Dominiak, Rumišek et Rupp, sp. nov. The male of North African S. incerta is described for the first time. Schizohelea algeriana and S. clastrieri are described from northern Algeria, and S. withersi from southern France. An identification key to all species of the genus is provided.